Enhancing decision quality through computer-based decision aids: how promotional interventions and Need for Cognition shape effectiveness in online consumer choices - Vogrincic-Haselbacher, Claudia; Behlau, Isabelle; Krueger, Joachim I.; Corcoran, Katja; Lurger, Brigitta; Athenstaedt, Ursula (Frontiers in Psychology, 2025)
IntroductionConsumers increasingly face overwhelming amounts of information when making online contractual decisions, particularly as e-commerce continues to expand the scope and complexity of available information. While this digital transformation promises greater transparency, many consumers struggle to process complex information effectively, leading to suboptimal decision making.MethodsIn a simulated online contracting scenario (N = 206), we investigated whether providing and promoting computer-based decision aids (CDA) could enhance decision quality. Additionally, we examined how individual differences in Need for Cognition (NFC), a trait characterizing one's tendency to engage in and enjoy effortful cognitive activities, moderates CDA effectiveness.ResultsWe find that promotional nudges increase the adoption of CDA and that they subsequently improve decision quality. These benefits are primarily seen among participants with low NFC, suggesting that decision aids are most valuable for individuals less inclined toward systematic information processing.DiscussionThese findings have significant implications for personalizing digital decision support systems and advancing consumer protection in increasingly complex online marketplaces.